Leverage, balance sheet size and wholesale funding - H. Evren Damar; Césaire A. Meh; Yaz Terajima (Bank of Canada, 2010)
Some evidence points to the procyclicality of leverage among financial institutions leading to aggregate volatility. This procyclicality occurs when financial institutions finance their assets with non-equity funding (i.e., debt financed asset expansions). Wholesale funding is an important source of market-based funding that allows some institutions to quickly adjust their leverage. As such, financial institutions that rely on wholesale funding are expected to have higher degrees of leverage procyclicality. Using high frequency balance sheet data for the universe of banks, this study tries to identify (i) if such a positive link exists between the assets and leverage in Canada, (ii) how wholesale funding plays a role for this link, and (iii) market and macroeconomic factors associated with this link. The findings of the empirical analysis suggest that a strong positive link exists between asset growth and leverage growth, and the use to wholesale funding is an important determinant of this relationship. Furthermore, liquidity of several short-term funding markets matters for procyclicality of leverage.
Keywords: G21; G28; 330; Financial stability; Financial system regulation and policies; Recent economic and financial developments; Finanzmarkt; Bank; Kapitalstruktur; Kanada